P~NDIDIKAN KEWARGANEGARAAN (PKn) MENJAWAD T·ANTANGAN MASA DEPAN KE ARAH INTEGRASI BANGSA - L. Hendrowibowo, L. Hendrowibowo (Jurnal Cakrawala Pendidikan, 2001)
Recently' "SARA" cases appear to the direction ofnation disintegration ofcourse influencesthe learning in th~ school, which ,is not good. One of the lessons that close relationship with thisproblem .i~ Religion Education and Civics Education. That is why according team nationalEducation":Departement needs the learning system in Civics Education.The: lean:llng process of Civics Education with the paradigm is hoped can give the newinspiration for ".teacher to development the student capacity ti the nation integration and sicialconcern. TIle "new paradigm is shoed in the way of learning that is used in the Civics Education,that the process.is very important. This case is different with the "Moral Pancasila" Education, thelatter is nearly like an indoctrination.The strategy which is used in giving material of Civics Ed.ucation directed to the knowingand doing with values clarification method, problem solving and inquiry. On the hand forevaluation using direct observation, not only cognitifevaluation, but al~o afectifand psychomotor.